Social Construction of Society in the Decrease in the Electricity of Female DRPD Members in the 2024 Election in Magelang Regency - Aulia Zabrina; Yayi Putri Dwihayuni; Inayat Ullah (Journal of Religion, Local Politics, and Law, 2026)
This study aims to analyze the social construction underlying the decline in the electability of female DPRD members in Magelang Regency in the 2024 Election. Based on election data, women's representation in the Magelang R egency legislature shows a less than optimal trend even though the affirmative action policy (30% quota) has been implemented in the nomination process. This study uses a descriptive qualitative method with the Social Construction theory of Peter L. Berger and Thomas Luckmann to dissect how women's political reality is shaped through the processes of externalization, objectification, and internalization in society. The results show that the decline in electability is influenced by social construction that is still dominated by patriarchal values, where political leadership is still constructed as a male domain. The main inhibiting factors include: (1) societal stigma that limits women's political space, (2) public perception of women's low political capabilities, and (3) the lack of social and economic capital of female candidates compared to male candidates. The conclusion of this study emphasizes that formal policies alone are not enough without being followed by a deconstruction of public perceptions of gender roles in politics.